2018
DOI: 10.1186/s12872-018-0952-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cardiac amyloidosis: a systematic review on the role of imaging and biomarkers

Abstract: BackgroundCardiac Amyloidosis (CA) pertains to the cardiac involvement of a group of diseases, in which misfolded proteins deposit in tissues and cause progressive organ damage. The vast majority of CA cases are caused by light chain amyloidosis (AL) and transthyretin amyloidosis (ATTR). The increased awareness of these diseases has led to an increment of newly diagnosed cases each year.MethodsWe performed multiple searches on MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews. Several search term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 98 publications
2
58
0
3
Order By: Relevance
“…These data shows that occurrence of AL and its severity significantly affect the survival of patients with MM, even in the current new drug era. 2,12,[16][17][18][19][20][21][22][23][24][25][26] Although a high level of baseline 24-hour proteinuria has been proposed as a marker of renal involvement and progression of renal dysfunction, our current research data showed that kidney involvement does not have a major impact on survival, similar to existing research results. 2,21 Forty-eight percent of patients who showed abnormal genes of TP53 deletion, and t(14;16) and 1q21 amplification had shorter OS than other patients (8 vs. 26.5 months), favoring the adverse effects of these high-risk genes on survival.…”
Section: Discussionsupporting
confidence: 88%
“…These data shows that occurrence of AL and its severity significantly affect the survival of patients with MM, even in the current new drug era. 2,12,[16][17][18][19][20][21][22][23][24][25][26] Although a high level of baseline 24-hour proteinuria has been proposed as a marker of renal involvement and progression of renal dysfunction, our current research data showed that kidney involvement does not have a major impact on survival, similar to existing research results. 2,21 Forty-eight percent of patients who showed abnormal genes of TP53 deletion, and t(14;16) and 1q21 amplification had shorter OS than other patients (8 vs. 26.5 months), favoring the adverse effects of these high-risk genes on survival.…”
Section: Discussionsupporting
confidence: 88%
“…In the diagnostic workup of cardiac amyloidosis, nuclear imaging with bone tracers, including [99mTc]‐DPD and [99mTc]‐PYP, may reliably detect ATTR amyloidosis and discern it from AL type …”
Section: Imaging Before or After Dischargementioning
confidence: 99%
“…73 In the diagnostic workup of cardiac amyloidosis, nuclear imaging with bone tracers, including [99mTc]-DPD and [99mTc]-PYP, may reliably detect ATTR amyloidosis and discern it from AL type. 74 Labelling of metaiodobenzylguanine with radioactive 123-iodine (123I-MIBG) enables scintigraphic visualization of the pre-synaptic sympathetic nerve endings and depicts the status of cardiac innervation, which is associated with the prognosis of HF patients. [75][76][77] Of note, according to 123I-MIBG imaging, a temporary decrease of norepinephrine uptake in the myocardium is typical for an exacerbation of HF and may be a potential therapeutic target.…”
Section: Stress and Nuclear Imagingmentioning
confidence: 99%
“…The strengths of their study were the large subject numbers, the use of a standardized analysis algorithm and relative simplicity of the measurements (which can be easily assessed by the human eye). All patients had cardiac MR scans in addition to echocardiography, an important factor given that gadolinium MR scanning is sensitive to identifying cardiac amyloid, a condition estimated to occur in ~25% of HF in patients aged >80 years (autopsy data), is often missed by clinicians and is less responsive to guideline‐based medical therapy …”
mentioning
confidence: 99%
“…All patients had cardiac MR scans in addition to echocardiography, an important factor given that gadolinium MR scanning is sensitive to identifying cardiac amyloid, a condition estimated to occur in~25% of HF in patients aged >80 years (autopsy data), is often missed by clinicians and is less responsive to guideline-based medical therapy. 10 Limitations of the study were the ASV randomization; the lack of oronasal flow (patients with HF often hyperventilate and need to mouth breath); and lack of measures of sleep quality, lung function, autonomic activity and ventilation (PaCO 2 ), which might also possibly contribute to prognosis. Moreover, oximeter settings (averaging time and storage capacity) can affect the placement of the SpO 2 nadir in relation to CSR and thus LPCT.…”
mentioning
confidence: 99%